Effectiveness of a Capacity Building Program on Basic Cardiopulmonary Resuscitation (CPR) Upon the Level of Knowledge and Skill among Taxi Drivers at Selected Areas in Tamil Nadu and Assam - D, Sasikala. (International Journal of Psychosocial Rehabilitation, 2020)
Background: The initial few minutes following an emergency—be it a heart attack, stroke, accident, or fit—are known as the ‘Golden Hour’ and truly so because the quality of care provided during this period has a direct bearing on the final outcome in an emergency. Aims: This study was done to assess the effectiveness of a capacity-building program regarding basic cardiopulmonary resuscitation (CPR) upon the level of knowledge and skill among taxi drivers. Materials and methods: A pre-experimental study was carried out among 140 taxi drivers working in selected areas of Tamil Nadu and Assam for a period of 6 weeks. The results were assessed using the pairedired t test, Pearson’s correlation,, and chi square. Results: The study results revealed that there was a significant improvement in the post-knowledge score of the taxi drivers in Tamil Nadu and Assam compared to the pretest, with a a ‘t’ value of 18.912 an13.84,84respectively,y atthe p